SEJARAH PEMIKIRAN DAN PENOMENA ORMAS PERSATUAN ISLAM DALAM DAKWAH ISLAMIYAH - surya darma darma (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2023)
This research discusses the history of thought and the Da'wah Persis Movement. In it, it is discussed how Persis views things related to Islamic thought and how Persis acts in preaching it. Persis also has a special council called the Hisbah Council which is the spearhead in determining ijtihad relating to religious thought. The method used is based on library research. So that various kinds of books were collected that discussed the Da'wah Persis movement. From this research it was concluded that Persis's contribution in the world of thought and Da'wah Islamiyyah in Indonesia since the founding of this organization was enormous. Persis has contributed to coloring the thought and proselytizing movement in Indonesia.